Tinjauan Hukum Penggunaan Debt Collector dalam Penagihan Hutang - Anggraeni, Amelia (UM Purwokerto Press, 2024)
Third party debt collectors provide collection services which are usually used by financial institutions to carry out credit collections. Large financial institutions such as banks have hundreds or even thousands of customers they must serve. The large number of customers makes it difficult for these financial institutions to serve customers internally. Of the many customers we have, there are quite a few customers who are disobedient or even default on the agreements they have made. Because of this inability, most large-scale financial institutions such as banks will ask for help from third parties to replace them in providing services to customers. One of the third parties whose services are used is a debt collector or what is usually called a debt collector. This third party moves to collect debts from debtors who are in default on the loans they have made. This research aims to analyze the legal view or juridical review of debt collectors who collect debts from debtors.